2019
DOI: 10.1111/imm.13099
|View full text |Cite
|
Sign up to set email alerts
|

The Autoimmune Regulator (Aire) transactivates HLA‐G gene expression in thymic epithelial cells

Abstract: Summary The Autoimmune Regulator (Aire) protein coordinates the negative selection of developing thymocytes by inducing the expression of hundreds of tissue‐specific antigens within the thymic medulla, which is also a primary site of the expression of the immune checkpoint HLA‐G molecule. Considering the immunomodulatory properties of Aire and HLA‐G, and considering that the role of the constitutive thymus expression of HLA‐G has not been elucidated, we studied the effect of AIRE cDNA transfection on HLA‐G exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 84 publications
(197 reference statements)
1
13
0
Order By: Relevance
“…Additionally, Gotter et al showed that human mTECs express a highly diverse selection of tissue-specific genes colocalized within chromosomal clusters: encompassing autoantigens and placenta-associated antigens including CGA, PRG2, SDC1, SEMA3B, CHS2, and CLDN4 ( 89 ). Recently, HLA-G was postulated to be regulated by Aire, consistent with earlier findings that identified a subset of TECs sharing expression of this placenta-specific gene with placental trophoblast cells ( 90 , 91 ). Therefore, it is possible that these antigens, when expressed by mTEC, help shape the mature T cell repertoire, including that of tT Regs that are recruited to the maternal-fetal interface and uterus-draining LN to monitor and provide tolerance to the developing fetus.…”
Section: Is There a Role Of Maternal Thymic Aire In Immune Tolerance supporting
confidence: 76%
“…Additionally, Gotter et al showed that human mTECs express a highly diverse selection of tissue-specific genes colocalized within chromosomal clusters: encompassing autoantigens and placenta-associated antigens including CGA, PRG2, SDC1, SEMA3B, CHS2, and CLDN4 ( 89 ). Recently, HLA-G was postulated to be regulated by Aire, consistent with earlier findings that identified a subset of TECs sharing expression of this placenta-specific gene with placental trophoblast cells ( 90 , 91 ). Therefore, it is possible that these antigens, when expressed by mTEC, help shape the mature T cell repertoire, including that of tT Regs that are recruited to the maternal-fetal interface and uterus-draining LN to monitor and provide tolerance to the developing fetus.…”
Section: Is There a Role Of Maternal Thymic Aire In Immune Tolerance supporting
confidence: 76%
“…Therefore, the presence of tolerogenic mechanisms is fundamental, such as the AIRE transcription factor, which allows negative selection of developing thymocytes. According to this, Melo-Lima et al (5) have been able to prove that this factor up-regulates HLA-G expression in thymic cells, limiting autoimmune diseases (59).…”
Section: Hla-g and Autoimmunitymentioning
confidence: 92%
“…1 HLA-G HLA-G is a non-classical HLA class I gene that encodes a molecule with tolerogenic properties (1). This molecule shows restricted tissue expression pattern, and was initially observed in extravillous cytotrophoblasts, where it plays an important role in the maintenance of fetal-maternal immune tolerance (2); it has also been observed in few healthy immune-privileged tissues, as cornea (3) and thymic medulla (4,5). However, HLA-G expression has also been reported in some pathological conditions, such as cancer and autoimmunity.…”
mentioning
confidence: 99%
“…Considering the immunoregulatory properties of the HLA‐G molecule, it seems sound to analyse its implication in autoimmune diseases. In fact, a recent study (Melo‐Lima et al., 2019) pointed out a tight link between Autoimmune Regulator (AIRE) gene and HLA‐G: Aire promoted the transactivation of HLA‐G gene by increasing the overall transcription and, thus, affecting the acceptance of self‐antigens. In this aspect, the study of HLA‐G polymorphisms in autoimmune diseases is relevant and both positive and negative associations have been reported (Gautam et al, 2019).…”
Section: Hla‐g and Diseasementioning
confidence: 99%